Digital Student Worksheet Oriented to Problem-Based Learning in Science Subjects for Elementary School Students - Supriatna, A.R.; Andriani, Riliana; Usman , Herlina; Sari, Yofita (Universitas Pendidikan Ganesha, 2024)
Teachers have difficulty developing learning tools, one of which is a student work sheet. The evolution of the times demands that teachers make use of existing technology. Therefore, it is necessary for the innovation and creativity of teachers to create interesting and enjoyable learning. The research was conducted with the aim of developing a problem-solving-based digital Students Working Sheet on IPA subjects for the highest grade that is valid and implementable. The type of research used is Research and Development (R&D). A total of 32 V-class students are subject to research. To test the level of validity of researchers involved media experts, material experts, and also linguists. Data is collected through observations, interviews to obtain needs analysis, and the dissemination of questionnaires. As for the percentage of the results of the qualification test, several expert judgements were obtained, among others: the media expert scored a presentation score of 92.50%, the material expert scared a presentation of 97.50% and the linguist scored the presentation of 87.50%. While the one-to-one test results scored 89.17% next step the researchers conducting a small group test scored 91.33% included in the very good category. In general, the digital learner work sheet can be used as a supporting teaching material in the learning of IPA in particular in the class V of the Basic School which can be done independently and give implications to the teacher of the Elementary School as well as further researchers to develop teaching materials in particular the digital LKPD based on PBL.